The Philippines' Service Industry The Three Major Influences on GDP. - Erika Mae Engracia; Rayniel Ryan Garcia; Bianca Turla; Marie Antoinette Rosete (UJoST- Universal Journal of Science and Technology, 2022)
The study aims to determine the relationship between the total growth rate of the service sector, gross value-added of the service sector, and total employment contribution in the service sector (independent variables) on the Philippines' GDP (dependent variable). Numerous studies show a relationship between the independent variable, Total Growth Rate, Employment Contribution and Gross Value Added of the Service Sector to the dependent variable, Gross Domestic Product of the Philippines. The researchers demonstrate the strong positive relationship between the total employment contribution and gross value added (GVA) of the service sector to the GDP of the Philippines as well as the weak positive relationship between the service sector economic growth rate using the Pearson Coefficient Correlation test. The group utilized available data from credible sources from the year 1990-2020.